STUDY ON THE INFLUENCE OF IRON ALLOY ATOM CONCENTRATION ON SODIUM INTERCALATION VOLTAGE AND REDOX MECHANISM IN SODIUM-ION BATTERY CATHODE NA?V???FE?(PO?)? - Ilman Huda Isyfi, Afthon
Sodium Vanadium Phosphate (Na?V?(PO?)?) with a NASICON (Na Super Ionic Conductor) structure is a promising candidate for sodium-ion batteries (NIBs) due to its high performance, exceptional structural stability, and abundance of raw materials. However, its primary challenge lies in replacing vanadium (V), which is expensive and toxic, with more economical elements such as iron (Fe). Fe doping strategies in NVP cathodes have demonstrated the potential to enhance intercalation voltage, significantly impacting the electrochemical performance of sodium-ion batteries. In this study, a quantum mechanical modeling approach based on Density Functional Theory (DFT) was employed to investigate the effects of substituting vanadium (V) with iron (Fe) atoms on the intercalation voltage of NVP. The focus was to determine the most thermodynamically stable phases for pure NVP and Fe-doped NVP, NayV2?xFex(PO?)? (NVFP), at various Fe doping levels (x = 0.25, 0.5, and 1) and Na compositions (y = 1, 2, 3, 4). According to formation energy calculations, the Na?V?(PO?)? configuration was found to be the most stable during the desodiation process, particularly with 50% Fe doping. Increasing Fe content in the NVP cathode resulted in a broader intercalation voltage range. The most significant increase in the voltage range compared to pure NVP (1.38 to 2.14 V) was observed with 50% Fe substitution (1.84 to 3.49 V). The addition of 25% and 50% Fe caused Fe 3d orbitals to dominate near the Fermi level, making iron the primary redox-active cation during the initial stages of desodiation, thereby enhancing the intercalation voltage of the NVP cathode. This study demonstrates that incorporating iron into the NVP cathode is an effective strategy for tuning the intercalation voltage range of NVP, which can be tailored to meet specific application requirements. With these improvements, Fe-alloyed NVP emerges as a promising option for high-performance sodium-ion battery cathodes. Keywords: sodium-ion battery, NASICON, cathodes, doping, electrochemical performance.